Peer teasing experiences of fathers and their children: Intergenerational associations and transmission mechanisms. (December 2018) - Kerr, David C.R.; Gini, Gianluca; Owen, Lee D.; Capaldi, Deborah M.
Abstract: Being the victim or perpetrator of peer teasing threatens children's immediate and long-term well-being. Given that many individual and contextual risk factors for peer victimization are transmitted within families, we tested whether fathers' childhood victimization experiences were directly or indirectly (via poor parenting and poor child adjustment) associated with their children's increased risk for similar experiences. Generation two (G2) fathers ( n = 130) who had been assessed since age 9 years participated in an intergenerational study with their 268 G3 children and the 163 G2 mothers of these children. Peer teasing ratings were collected annually from G1 mothers, fathers, and teachers across G2 ages 9–16 years, and from the same three informant types across the same ages for G3 children. Also assessed was G2 fathers' poor parenting of G3 at ages 3–7 years and G3 poor adjustment (externalizing and internalizing behaviors, deviant peer association, low social competence) and body mass index (BMI) at ages 7–16 years. Models supported intergenerational stability in being teased that was partially mediated through G2 fathers' poor parenting and G3 poor adjustment. A direct intergenerational path in being teased remained significant, and G3 BMI uniquely predicted being teased. Childhood peer victimization is perpetuated across generations. Prevention aimed at poor parenting, child poor adjustment, and peer victimization itself may disrupt intergenerational stability in these adverse experiences.